Cash for transactions or store-of-value? A comparative study on Sweden and peer countries - Carl Andreas Claussen; Björn Segendorff; Franz Seitz (Sveriges Riksbank, 2023)
We estimate the demand for transaction and non-transaction cash balances in Canada, Denmark, Iceland, Sweden and Norway over the last decades using the seasonal method. These countries share many features that are relevant for cash demand, but nevertheless show large differences in terms of aggregate cash balances. While Canada, Iceland and Denmark have seen increased aggregate cash balances, Norway and especially Sweden have seen a dramatic decline. We find that transaction balances have decreased somewhat in all of the countries and the differences in aggregated cash balances is due to differences in the development of non-transactional cash balances. We argue that different de facto legal tender status, crisis exposures, foreign demand and cash supply-side policies help explain these findings.
Keywords: E41; E51; E58; 330; cash; banknotes; seasonal method; transactions; hoarding